Unraveling the Nexus: Social Spending, Development, and Breaking the Cycle of Poverty - Shehata, Yasmin (AUC Knowledge Fountain, 2024)
This study examines the role of development, as indicated by the Human Development Index (HDI), in shaping the connection between social public spending on health, education, and social protection and poverty in terms of the poverty headcount ratio at $3.65/day (2017 PPP). Empirical analysis is used to this end, employing a panel dataset of 68 countries at varied stages of development over the period 1995-2021. The empirical model is estimated using the Fixed Effects Two-stage Least Squares (2SLS). It is also re-estimated using the Instrumental Variable Generalized Method of Moments (IV-GMM) and Limited Information Maximum Likelihood (LIML) to test the robustness of the results. The 2SLS results reveal a significant negative effect of development on the effectiveness of social public spending to reduce poverty. In other words, the correlation between social public spending and poverty becomes more negative at higher HDI levels. These results are robust to different estimation techniques.